EVALUATION OF SUGARCANE HYBRID CLONES ON WEED DYNAMICS, SUGAR QUALITY AND PLANT CROP PRODUCTIVITY AT BADEGGI, NIGERIA - Bassey, M. S.; Shittu, E. A.; Lawan, Z. M.; Eze, J. N. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Plant breeding programme develop varieties primarily to increase yield and resistance to diseases/insects with little emphasis on weeds dynamics. This study was conducted to evaluate sugarcane hybrid clones for weed dynamics, sugar quality and plant crop productivity at the Upland Sugarcane Experimental Field of National Cereals Research Institute, Badeggi, Nigeria. A total of sixteen clones were planted on a Randomized Complete Block Design (RCBD) with three replications. Analysis of variance revealed significant differences among the clones for some traits. Our results show that P. scrobiculatum (Linn.), S. pumila (Poir.), P. leucanthus (Schum & Thonn), B. diffusa (L), H. suaveolens (Poit), C. esculentus (Linn.) and K. squamulata (Thorn.ex Vahl) were the major weed problems of sugarcane at Badeggi. Lower weed dry matter (0.18 g m-2), and taller plants (194.07 cm), higher cane yield (136.8 t ha-1) and Sugar yield (12.93 t ha-1) were found in BD -1098-003 m among the studied hybrids. BD 1098-005 m, BD 441-007 m and B 47419 possess higher fibre, these materials can be utilized for energy cane variety. Brix percent also varied among the clones with increase in crop age, which can be used as indicator for maturity. The results revealed that some weed species types and their duration of infestation are among the numerous factors responsible for the reduction in growth and yield attributes of sugarcane crop. The promising hybrids will be advance for more evaluation at different locations for yield and juice quality stability studies.